Les politiques culturelles dans l'Europe communautaire : l'évolution du cadre juridique - Cornu, Marie; de Lamberterie, Isabelle (Études internationales, 1996)
What place does Europe reserve for culture? In particular, does the legal framework make it possible for the cultures of member states to develop in the respect of their diversity, as stipulated in the Union Treaty ? We can, of course, prefer a generous vision of a composite Europe, where ideas circulate freely, as well as their creators and the latter's works. Given the European community's founding principles, we are tempted to see the EU'S legal order as the natural setting for the diffusion of European cultures. But the EU'S rationale mainly focusses on building a single market in a single space. From this angle, the perspective is not so idyllic. Although certain cultural goods can also be seen from an economic viewpoint (in that they are intended for circulation in commerce), their cultural value should not be overlooked. How does EU law handle this question ? Economic and cultural interests are not always compatible with each other. Under what circumstances does cultural specificity require a solution different from an economic one ? Does EU law really take into account the dimension of culture in the pursuit of its principal objectives ? All these questions receive different answers depending on the type of legislation (whether about taxation, authors' rights, the circulation of works of art). Given current legal texts, we can but hope for more awareness whenever cultural interests are at stake.